Do thinking styles play a role in whether people pathologise their pornography use? - Duffy, Athena (2016)
Introduction: The concept of pornography addiction, although widely accepted, continues to be debated, and as such no diagnostic criteria exist. Opponents and proponents of pornography continue to cite evidence that supports the claim that pornography is either harmful or beneficial, respectively. However, a review of the literature pertaining to pornography use revealed conceptual and methodological shortcomings which limit the conclusions made in the existing literature base. Without adequate research to further our understanding of the complex relationship individuals have with pornography, we risk pathologising or condoning behaviours that are legal and consensual, which may cause distress for some individuals, or even divert attention from deeper issues, such as an individual’s thinking styles and feelings of shame. Researchers acknowledge that people’s relationship with pornography is complex (Hardy, 1998) and individuals experience it in different ways, for example the time spent viewing pornography, the environment in which they view it, who they view it with, and the genre of pornography they watch (Attwood, 2005; Hald & Malamuth, 2008; Malamuth, Addison, & Koss, 2000; Poulsen, Busby, & Galovan, 2013; Reid, Li, Gilliland, Stein, & Fong, 2011). Given that additional variables may be involved when people pathologise their pornography use, particularly rigidity of thinking (Reid et al., 2009), it is worth investigating such variables further to help discern differences between those who pathologise their pornography use and those who do not.